Enzymes of type II fatty acid synthesis and apicoplast differentiation and division in Eimeria tenella. - Ferguson, D; Campbell, SA; Henriquez, F; Phan, L; Mui, E; Richards, T; Muench, S; Allary, M; Lu, J; Prigge, S; Tomley, F; Shirley, M; et al. (2007)
Apicomplexan parasites, Eimeria tenella, Plasmodium spp. and Toxoplasma gondii, possess a homologous plastid-like organelle termed the apicoplast, derived from the endosymbiotic enslavement of a photosynthetic alga. However, currently no eimerian nuclear encoded apicoplast targeted proteins have been identified, unlike in Plasmodium spp. and T. gondii. In this study, we demonstrate that nuclear encoded enoyl reductase of E. tenella (EtENR) has a predicted N-terminal bipartite transit sequence, typical of apicoplast-targeted proteins. Using a combination of immunocytochemistry and EM we demonstrate that this fatty acid biosynthesis protein is located in the apicoplast of E. tenella. Using the EtENR as a tool to mark apicoplast development during the Eimeria lifecycle, we demonstrate that nuclear and apicoplast division appear to be independent events, both organelles dividing prior to daughter cell formation, with each daughter cell possessing one to four apicoplasts. We believe this is the first report of multiple apicoplasts present in the infectious stage of an apicomplexan parasite. Furthermore, the microgametes lacked an identifiable apicoplast consistent with maternal inheritance via the macrogamete. It was found that the size of the organelle and the abundance of EtENR varied with developmental stage of the E. tenella lifecycle. The high levels of EtENR protein observed during asexual development and macrogametogony is potentially associated with the increased synthesis of fatty acids required for the rapid formation of numerous merozoites and for the extracellular development and survival of the oocyst. Taken together the data demonstrate that the E. tenella apicoplast participates in type II fatty acid biosynthesis with increased expression of ENR during parasite growth. Apicoplast division results in the simultaneous formation of multiple fragments. The division mechanism is unknown, but is independent of nuclear division and occurs prior to daughter formation.